The determination of the best operating parameters for a small SI engine fueled with methanol gasoline blends - SAYIN, CENK (ELSEVIER, 2021)
It is extremely important to ensure a clean and sustainable energy supply due to the decreasing fossil energy resources, their increasing costs and irreversible damages on the ecological balance. Considering this situation, this study focuses on the determination of the best operating parameters for a small spark ignition (SI) engine fueled with methanol/gasoline blend (M5, M10, M15 and M20). Moreover, operating conditions are optimized according to different weights between performance and emission. In the first stage of the study, engine tests were carried out at different loads (10 and 20 Nm) and compression ratios (CR) (7:1, 8:1 and 9:1) and the changes in engine performance and exhaust emissions were presented. In addition, these experimental results were used in optimization. According to the engine test results, performance and emissions of small SI engine were generally improved with increasing the methanol ratio in the blend fuels under all experimental conditions. When exhaust emissions were evaluated, it was observed that M20 was more favorable than gasoline if it was used in CR of 9:1 in a small SI engine. In the second stage of the study, the effect of experimental variables on the experimental results was statistically investigated with analysis of variance (ANOVA). The results of ANOVA analysis showed that all experimental variables were statistically significant for both engine performance and exhaust emissions. In the last stage of the study, the operating conditions of the engine were optimized according to eleven different weight ratios between performance and emissions, with a multi-criteria decision-making method based on grey relational analysis (GRA). According to the optimization results, the most suitable operating parameters were presented to the readers with regard to the desired weight ratio in engine performance and exhaust emission. The presented optimization model can be used for the design of electronic fuel systems for alternative fuel engines. Moreover, suitable engine parameters determined according to the selected weight ratio can also be adjusted structurally in the engine.
Keywords: Exhaust emission; Small SI engine; Sustainable fuels; Engine performance; Compression ratio; Methanol; MULTIOBJECTIVE OPTIMIZATION; COMBUSTION CHARACTERISTICS; UNREGULATED EMISSIONS; PERFORMANCE; ETHANOL; HYDROGEN; BUTANOL; POWER